ANALYSIS OF FORMS OF PUNISHMENT IN ASBABUN NUZUL VERSES ABOUT THE PROHIBITION OF ADULTERY - Lukman, Lukman; Yusam Thobroni, Ahmad; Miftahus Sudury, Ahmad (Al - Tadabbur: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
Islam teaches ethical norms in life. One of these norms is the prohibition of committing adultery, as stated in the Qur’an. Adultery is an immoral act that is forbidden by Allah SWT. However, there are still individuals in society who engage in adultery due to various factors, such as an inability to control their desires and a lack of faith. The purpose of punishing those who commit adultery is to protect their dignity as servants of God. This literature research uses a descriptive-qualitative method. The data is obtained from representative literature sources, followed by content analysis and concluding the findings. The research results show that the punishment for unmarried offenders (ghairu muhsan) is flogging one hundred times and exiling them for one year, while the punishment for married offenders (muhsan) is stoning until death.